Etnicidad vs. aculturación : las necrṕolis castellanas de los siglos V-VI d.C. y el asentamiento visigodo en la Península Ibérica : una mirada desde la meseta sur - Barroso Cabrera, Rafael (Access archaeology., 2018)
A study of the political and archaeological controversies surrounding the Castilian Necropoleis of the V-VI Centuries AD and the Visigoth Settlement in the Iberian Peninsula. The author attempts to deconstruct the various controversies and presents fresh analysis based on the archaeological data and literary evidence.